Analyzing Student's Motivation Towards Science Learning in Junior High School - Anidya Diva Nuraysha; Nanang Winarno; Wirawan Fadly; Lukman Hakim; Emiliannur Emiliannur (Jurnal Penelitian Pendidikan IPA, 2024)
Motivation is one of the factors that influence student learning outcomes, especially science learning. Motivation has an impact on the results of students' learning and must be concerned to enhance student motivation. This research aims to investigate Junior High School students' motivation in science learning. The survey method, which is a quantitative research method, was used in this research. The instrument named Students' Motivation Towards Science Learning Questionnaire (SMTSLQ), and open-ended questions were applied to Junior High School students who studied in Junior High School, West Java, Indonesia. The participants of this research are 1018, with 622 female and 396 male students. The collected data was analyzed with descriptive statistics, then supported by the answers to open-ended questions from the students. The findings showed that the average self-efficacy is 3.38, active learning strategies is 3.83, science learning value is 3.68, performance goal is 2.9, achievement goal is 3.69, and learning environment stimulation is 3.39. The total average is 3.52, which means the students in Junior High School are categorized as having a high level of motivation in science learning. Based on the students' answers to open-ended questions, they are motivated to learn science because science is fun and interesting to learn, and teachers are able to provide experiences from experiments. Meanwhile, students who are not motivated to learn science because science is a complex subject and difficult to understand, and teachers who give a lot of assignments without experimentation